The prevalence of tumour markers in malignant pleural effusions associated with primary pulmonary adenocarcinoma: a retrospective study. Issue 1 (1st January 2021) - Fjaellegaard, Katrine; Koefod Petersen, Jesper; Andersen, Gitte; Biagini, Matteo; Bhatnagar, Rahul; Laursen, Christian B.; Clementsen, Paul Frost; Bodtger, Uffe
ABSTRACT: Background: Oncological treatment of primary pulmonary adenocarcinoma (AC) includes drugs targeting the pathways involving programmed death-ligand 1 (PD-L1), epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK). The aim of the study was to report the prevalence of these tumour markers in pleural fluid with cytology positive for pulmonary AC and the potential influence of volume pleural fluid tested. Methods: We retrospectively reviewed all thoracenteses performed in a two-year period at our interventional unit at Department of Respiratory Medicine at Zealand University Hospital Naestved, Denmark. ALK and PD-L1 testing was done using immunohistochemistry and EGFR testing using next-generation sequencing. We included pleural fluid specimens containing malignant cells originating from primary pulmonary AC and with at least one tumour marker requested by the clinicians. Results: When screening 927 pleural fluid specimens, we identified 57 in accordance with the inclusion criteria. PD-L1, ALK and EGFR were obtained in 35/55 (64%), 38/57 (67%) and 26/47 (55%), respectively. The prevalence did not increase when analysing volumes > 50 mL ( p = 0.21–0.58) Conclusion: Tumour markers in pleural fluid specimens containing cells from pulmonary AC can be demonstrated in more than half of the cases. Therefore, supplementary invasive procedures than thoracentesis could potentially await these analyses.